FREKUENSI SOIL TRANSMITTED HELMINTHS PADA SISWA SEKOLAH DASAR NEGERI NO. 32 MUARA AIR HAJI KECAMATAN LINGGO SARI BAGANTI PESISIR SELATAN - Zulita, Fitria Nelda; Indriati, Gustina; Lusi, Armein (STKIP PGRI Sumbar, 2013)
ABSTRACT Intestinal helminth infections which transmitted through soil (Soil Transmitted Helminths) is it still a health problem in public Indonesia. Intestinal parasitic worm infections are generally age children of primary school, it was caused have not been able to control the hygiene and healthy. In the elementary School 32 Muara Air Haji, it is located in Linggo Sari Baganti, district Pesisir Selatan. Livelihoods of fishermen and the generally as the average economic low level and medium level. Most people in this Nagari Muara Air Haji does not have BAB / WC is ± 54.41 %. In that regard it has been studied in order to determine the frequency of Soil Transmitted Helminths Primary School Students 32 Muara Air Haji Linggo Sari Baganti district pesisir selatan. The research was conducted in June 2013 with using a descriptive survey method. The population in this study was elementary school student No. 32 Muara Air Haji as 135 people . Sampling was done by random sampling from a population of 68 peoples. Stool examination conducted at the Laboratory of Biology Education Program STKIP PGRI West Sumatra by way of direct observation. The results showed elementary school students No. 32 Muara air haji that has been infected Soil Transmitted Helminths was76.47 %, with 36.54 % details of Ascaris lumbricoides, Trichuris trichiura 28.85 %,1.92 % Hookworm, Ascaris lumbricoides and Trichuris trichiura 28.85 %, Trichuris trichiura and Hookworm 1.92 %, then Ascaris lumbricoides, Trichuris trichiura and Hookworm 1.92 %. Highest frequency of Soil Transmitted Helminths found that Ascaris lumbricoides.